Analisis Pemeliharaan Sumber Daya Manusia Kesehatan (SDMK) di PT Tirta Medical Indonesia - Zebua, Cynthianoor Fitriana Puteri; Deviyanti, Dira; Ardhila, Diva; Salsabila, Lutfiyah Nada; Safitri, Safitri; Yuriska, Yuriska; Gurning, Fitriani Paramita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Maintenance of human resources is very important for every company, because besides aiming to maintain human resources it can also increase employee dedication, discipline and loyalty. Maintenance of human resources will protect workers from work accidents and maintain harmonious communication between human resources. The type of research used in this research is qualitative type research and the approach used in this research is a deductive approach, where the informants provide explanations about the principles of learning content, then explain them in the form of their application or examples in certain situations. The purpose of this study was to determine the procedures for carrying out the maintenance of human resource management at PT. Tirta Medical Indonesia. From the results of this study it can be seen that PT. Tirta Medical Indonesia has implemented good work maintenance methods and in accordance with the theory of Drs. H. Melayu S. P Hasibuan which includes effective communication between companies and employees, providing fair incentives, paying attention to employee welfare, occupational health and safety and conducting Pancasila industrial relations. The author suggests that PT. Tirta Medical Indonesia must continue to be able to maintain and improve the maintenance of better Human Resources in order to increase employee loyalty and performance. Keywords: Maintenance, Employees, Methods, Human Resources